Application of Phase-Reversal Fresnel Zone Plates for High-Resolution Robotic Ultrasonic Non-Destructive Evaluation; Sensors; Vol. 21, iss. 23 - Dolmatov D. O. Dmitry Olegovich; Tarrazo-Serrano D. Daniel; Filippov G. A. German Alekseevich; Uris A. Antonio; Sednev D. A. Dmitry Andreevich (2021, 2021)
Title screen